2021
DOI: 10.1002/pmrj.12552
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Provider‐Reported Satisfaction of Cancer Rehabilitation Telemedicine Visits During the COVID‐19 Pandemic

Abstract: Introduction The coronavirus disease 2019 (COVID‐19) pandemic has accelerated the growth of telemedicine services across the United States. In this study, we examined cancer rehabilitation patient and physician satisfaction with telemedicine visits. We also sought to evaluate the types of provider services that are given during telemedicine visits. Objective To assess overall patient and provider satisfaction with telemedicine visits and explore whether satisfaction var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 20 publications
6
58
1
5
Order By: Relevance
“…Another study of cancer rehabilitation found that telemedicine was generally viewed favorably, but that new or worsening problems were not as suitable to telemedicine according to patients or providers. 11 Among the general public, a survey by the COVID-19 Healthcare Coalition of n 5 2,007 patients who had a telehealth visit showed high satisfaction, in contrast to our study findings. 24 A majority of those responding to the Healthcare Coalition survey reported that telehealth maintained the patient-physician relationship, preserved continuity of care, removed barriers to accessing care, and reported high visit quality.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Another study of cancer rehabilitation found that telemedicine was generally viewed favorably, but that new or worsening problems were not as suitable to telemedicine according to patients or providers. 11 Among the general public, a survey by the COVID-19 Healthcare Coalition of n 5 2,007 patients who had a telehealth visit showed high satisfaction, in contrast to our study findings. 24 A majority of those responding to the Healthcare Coalition survey reported that telehealth maintained the patient-physician relationship, preserved continuity of care, removed barriers to accessing care, and reported high visit quality.…”
Section: Discussioncontrasting
confidence: 99%
“…1,[11][12][13] Still, many patients both before and during the pandemic reported high satisfaction with telehealth visits, suggesting a potential role for virtual visits even after pandemic conditions relax. 11,13 Other studies have started to outline how cancer care might be redefined postpandemic to better serve both patients and providers. 14,15 Given the emerging literature on experiences with telehealth and preferences for future care, we set out to understand both provider and cancer survivor experiences with telehealth and to solicit feedback on how to maximize the contributions of telehealth services that can improve quality of cancer care during and after the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ability of the participants was improved by the system’s repetitive balance exercises to acquire confidence and motor skills in postural control, which could improve daily task performance. Authors in [ 92 ] assessed patients and providers’ satisfaction of cancer tele-rehabilitation visits during the COVID-19 pandemic. A cancer rehabilitation program was developed at an academic medical centre.…”
Section: Taxonomymentioning
confidence: 99%
“…Other studies also showed overall good patients’ acceptance regarding the implementation and use of telehealth during the COVID-19 pandemic, among others, for reasons, such as travel time, travel expense, and convenience [ 23 , 26 ]. Especially cancer patients receiving active treatment seem to have adjusted quickly to the use of telehealth considering their overall satisfaction about their telehealth consultations [ 27 30 ]. An American study by Darcourt et al found that 92.6% of all cancer patients ( n = 1762) were satisfied with their telehealth consultations [ 31 ].…”
Section: Discussionmentioning
confidence: 99%